Strategi dan Peranan Orang Tua terhadap Pemerolehan Bahasa ABK dalam Komunitas Masyarakat Betawi - Wardani, Esti Tri; Siregar, Iskandarsyah; Susanto, Arju; Hamzah, Nurul Huda; Yahya, Samsur Rijal (Universitas Muhammadiyah Surabaya, 2025)
Parents play a significant role in the language acquisition process of children with special needs. This study aims to investigate the strategies and roles that parents play in supporting the language acquisition process of children with special needs, specifically those with autism and mental retardation. The research used the descriptive qualitative technique with triangulation as the data collection method and analyzed the data using B.F. Skinner's behavioristic theory. The results indicate that children with disabilities face challenges at the morphological and syntactic levels of language acquisition. To support the language acquisition process, parents face challenges, provide appropriate treatment, and develop effective strategies. The challenges include communication, social stigma, learning consistency, limited resources, social interaction, and emotions and psychology. The resulting treatments and strategies aim to address these challenges.